Perancangan Fasilitas Kerja untuk Mengurangi Risiko Kerja Menggunakan Metode WERA dan Antropometri - Siti Siryana; Nugraha; Nur Rahman As'ad (Bandung Conference Series: Industrial Engineering Science, 2022)
Abstract. Dena Collection company is a home industry company engaged in producing women's bags. the employees at the Dena Collection company, are worked manually. However, at the pattern-making work station, cutting work station, also QC and packing work stations the employees often experienced complaints and the employees work without using the work facilities. The aims of this research were; 1) identifying the complaints of employees at the pattern-making, cutting, as well as QC and packing work stations, 2) identifying the work risks experienced by employees at the pattern-making, cutting, also QC and packing work stations, 3) determining the proposed work facility design at pattern-making, cutting, as well as QC and packing work stations. The methods used based on these conditions included the Nordic Body Map method to determine the level of complaints felt by employees while at work. The WERA method utilized to determine the level of risk experienced by employees and the steps that must be taken, The antropometri to determine the physical size of humans to make it easier to do a design. The research results obtained were; 1) the biggest complaint felt by employees was a pain of the body such as the necks, backs, wrists, and feet, 2) the work risks experienced by employees at the three work stations had a final score of 28-38 including in the medium level. 3) the proposed work facility design carried out at the three work stations, namely the facilities addition of two workbenches, the first workbench is used for the pattern-making work station and the cutting work station, the second workbench is used for the QC and packing work station. Abstrak.Perusahaan Dena Collection merupakan perusahaan home industry pembuat tas wanita. Pekerja di perusahaan Dena Collection bekerja secara manual, namun pada stasiun kerja pembuatan pola, stasiun kerja pemotongan, stasiun kerja QC & packing para pekerja sering mengalami keluhan dan pekerja bekerja tanpa menggunakan fasilitas kerja. Tujuan dari penelitian ini 1) Mengidentifikasi keluhan pekerja pada stasiun kerja pembuatan pola, pemotongan, QC & packing, 2) Mengidentifikasi risiko kerja yang dialami oleh pekerja pada stasiun kerja pembuata pola, pemotongan, QC& packing, 3) Menentukan usulan perancangan fasilitas kerja pada stasiun kerja pembuatan pola, pemotongan, QC & packing. Metode yang digunakan yaitu menggunakan metode Nordic Body Map untuk mengetahui tingkat keluhan yang dirasakan oleh pekerja pada saat sedang bekerja. Metode WERA untuk mengetahui tingkat risiko yang dialami oleh para pekerja serta langkah yang harus dilakukan. antropometri untuk mengetahui ukuran fisik manusia dan memudahkan dalam melakukan suatu perancangan. Hasil penelitian yang didapatkan adalah 1) Keluhan yang dirasakan oleh perkerja terbesar yaitu terdapat pada bagian tubuh seperti leher, daerah punggung, pergelangan tangan dan kaki. 2) Risiko kerja yang dialami oleh pekerja pada ketiga stasiun kerja memiliki skor akhir 28-38 termasuk dalam tingkatan sedang. 3) Usulan perancangan fasilitas kerja yang dilakukan pada ketiga stasiun kerja tersebut yaitu penambahan fasilitas kerja meja dengan 2 meja kerja, meja pertama digunakan untuk stasiun kerja pembuatan pola dan stasiun kerja pemotongan, meja kedua digunakan untuk stasiun kerja QC & packing.